2015
DOI: 10.1177/0363546515571918
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Acetabular Rim Recession on Anterior Acetabular Coverage

Abstract: The false-profile view is recommended in the perioperative workup for all patients undergoing arthroscopic treatment of pincer impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…It is suggested through in vivo and cadaveric studies that each 1 mm of rim resection results in 1°to 2°d ecreases in lateral and anterior center-edge angles [6,14,22]. However, cadaveric studies also show that rim resection of 4 mm increases the contact pressure within the hip [4] and that rim resection of as little as 3 mm can cause instability and subluxation of the hip [6].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested through in vivo and cadaveric studies that each 1 mm of rim resection results in 1°to 2°d ecreases in lateral and anterior center-edge angles [6,14,22]. However, cadaveric studies also show that rim resection of 4 mm increases the contact pressure within the hip [4] and that rim resection of as little as 3 mm can cause instability and subluxation of the hip [6].…”
Section: Discussionmentioning
confidence: 99%
“…A resection of 7.5 mm caused 50% of the specimens to become unstable and require an externally applied force to maintain hip joint reduction. 16 Philippon et al 8 found that 1 and 2 mm of rim resection correlated with a change in LCEA of 2.4 and 3.1 , respectively. In the current study, we found that the average difference in preoperative LCEA between symptomatic and unaffected acetabula was 8.5 , whereas the difference in anterosuperior rim thickness was 0.5 mm.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently controversy about normal and abnormal acetabular rim morphology and what radiographic or advanced imaging parameter or parameters are used to measure "normal." 7,16 Radiographic parameters alone have been shown to be poor predictors of pincer-type FAI. [3][4][5] CTbased studies and 3D studies have attempted to qualify and quantify normal and abnormal parameters for acetabular volume and morphology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations